Development of a compact 2.17 K hybrid 4He JT cryocooler for space applications. (September 2021) - Liu, Ziyao; Ma, Yuexue; Quan, Jia; Liu, Yanjie; Wang, Juan; Li, Jianguo; Liang, Jingtao
Highlights: A new four-stage oil-free JT compression system for space applications is developed to drive the space JT cooler. No-load temperature of 2.17 K is obtained by space closed-cycle JT cooler when 4 He is used as working medium. Cooling capacity of 4 mW at 2.39 K is achieved by the hybrid JT cooler. Abstract: The space 2 K cryogenic technology is one of the key supporting technologies for deep-space exploration. Superfluid helium cryostats were used to obtain the temperature below 2 K in early space missions. However, superfluid helium cryostats have been gradually replaced by space 2 K mechanical cryocoolers to reduce the weight of satellites and extend the lifetime of detectors. Recently, a space hybrid 4 He Joule-Thomson (JT) cryocooler operating at about 2 K is developed by our laboratory, which has a compact structure. The JT cycle, precooled by a two-stage thermally coupled pulse tube cryocooler (PTC), is driven by an efficient four-stage JT compression system. All the compressors used to drive the JT cycle and PTC in this hybrid JT cryocooler are designed for future space applications. This hybrid JT cryocooler reaches a minimum no-load temperature of 2.17 K and achieves the cooling capacity of 4.0 mW at 2.39 K.